How Does TeamSTEPPS Affect Operating Room Efficiency?. (8th December 2015) - Shams, Alexandra; Ahmed, Mostafa; Scalzitti, Nicholas J.; Stringer, Matthew; Howard, N. Scott; Maturo, Stephen
Abstract : Objective: To evaluate the effect of TeamSTEPPS (Team Strategies and Tools to Enhance Performance and Patient Safety) on operating room efficiency for the otolaryngology service at a tertiary care medical center. Study Design: Retrospective database review. Setting: Otolaryngology department at tertiary care medical center. Subjects and Methods: To assess the impact of implementing an evidence‐based patient safety initiative, TeamSTEPPS, on operating room efficiency in the otolaryngology department, the operative times, time lost to delayed starts, and turnover times during the year following the implementation of TeamSTEPPS were compared with the values from the prior year. Results: The study compared 1322 cases and 644 turnovers in the year prior to TeamSTEPPS implementation with 1609 cases and 769 turnovers in the following year. There were no statistically significant decreases in operating room efficiency in the year after the TeamSTEPPS rollout. Conclusion: Operating room efficiency was preserved after the rollout of a rigorous evidence‐based patient safety initiative that requires active participation from all operating room team members.